System identification and speed control of electro-mechanical dual acting pulley continuously variable transmission - Mohd. Azwarie Mat Dzahir, 1986- (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Doktor Falsafah (Kejuruteraan Mekanikal)) - Universiti Teknologi Malaysia, 2017